Strategi Diseminasi Informasi Publik oleh Humas Pemerintah Kota Bogor Melalui Media Sosial - Nuranijiwa, Nadila; Rici Tri Harpin Pranata (Pusat Riset dan Inovasi Nasional, 2025)
This study examines how the Public Relations Division (PROKOMPIM) of the Bogor City Government disseminates public information through social media, particularly Instagram, as part of its strategic communication efforts in the digital era. Using the theoretical framework of Government Public Relations (GPR) by Widodo Muktiyo (2020), this research highlights the essential role of government public relations in building public trust, ensuring transparency, and strengthening the positive image of government institutions. The study employs a qualitative descriptive approach to analyze communication strategies, message delivery, and audience engagement in the dissemination process. The findings show that social media serves as an effective and interactive medium for delivering accurate, relevant, and timely information to the public. Furthermore, the use of digital platforms allows PROKOMPIM to foster two-way communication, increase community participation, and enhance the credibility of local governance through more accessible, transparent, and responsive public communication.